Careers and Survival: Competition and Risk in the Hedge Fund and CTA Industry - Brown, Stephen J.; Goetzmann, William N.; Park, James (Journal of Finance, 2001)
ABSTRACT Investors in hedge funds and commodity trading advisors (CTAs) are concerned with risk as well as return. We investigate the volatility of hedge funds and CTAs in light of managerial career concerns. We find an association between past performance and risk levels consistent with previous findings for mutual fund managers. Variance shifts depend upon relative rather than absolute fund performance. The importance of relative rankings points to the importance of reputation costs in the investment industry. Our analysis of factors contributing to fund disappearance shows that survival depends on absolute and relative performance, excess volatility, and on fund age.